Recent Advances in Breast Cancer Diagnosis Entering an Era of Precision Medicine - Christopher Lim; Aung Mra; Chin Suliong; Challa Venkata Rao; Tun Aung; Jony Sieman; Win Tin; Maher F. Sefein Beshay; Alvin Oliver Payus; Meryl Grace Lansing; Mohammad Saffree Jeffree; Fairrul Kadir; et al. (2019)
This article will cover some of the most recent advances in the diagnosis of the world’s most common cancer in women, namely, breast cancer as we enter the era of precision medicine. The authors will discuss the differences between East and West pertaining to the incidence and mortality rates, the types of breast cancer and the revised staging criteria of breast cancer according to the American Joint Committee on Cancer (AJCC) Staging Manual, 8th edition. In addition, the advances of newer imaging modalities are presented and compared with traditional ultrasonography and mammography.